(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
In Les mots et les choses Foucault claims the character of Don Quixote to be the epistemic boundary between Renaissance and Âge classique. In these same terms, we aim to describe the evo-lution of the epic genre into the novel form, bringing the Foucauldian interpretation closer to that provided by Lukács’ Die Theorie des Romans, where Don Quixote is presented as the first modern novel. We will therefore refer to the 17th century as a moment of epistemic as much as social transition, to identify both in the emergence of the novel form, and in the madness of Don Quixote, the symptom of the crisis of the symbolic, social and political system that had justified the epic genre. This understanding will be applied to the analysis of the fragments of Don Quixote dedicated to the episode of the Master Pedro puppet show (II, cap. XXV-XXVI).